Genetics and Evolution of 2,4-Diacetylphloroglucinol Synthesis in Pseudomonas fluorescens - Troppens, D.; Moynihan, J.; Barret, M.; O'Gara, Fergal; Morrissey, J. (John Wiley & Sons, 2013)
Pseudomonas fluorescens is well known for the production of secondary metabolites. Some of these metabolites have potent antibiotic-type activity and it is generally assumed that these are produced as defense against soil predators or to aid competition for resources. 2,4-diacetylphloroglucinol (DAPG) is one such metabolite that is produced by a subset of P. fluorescens strains. DAPG-producing P. fluorescens strains are associated with natural biocontrol in agricultural soils and, as a result, the biosynthesis and genetics of DAPG production has been studied quite extensively. The basic biochemical pathway for synthesis of this modified polyketide is established, and the genes and regulators that direct synthesis have been cloned and analyzed for the past 20 years. DAPG production is under pathway-specific and global-regulatory control, most notably by the Gac/Rsm system. Despite our detailed knowledge of some aspects of the genetics of DAPG production, questions remain to be answered. This has become important, as new data that indicate that DAPG may play a role as a signal molecule in the rhizosphere have emerged. Several different lines of evidence suggest that P. fluorescens communicates with other bacteria and with plants via DAPG. It is therefore intriguing to consider how this function may have evolved and this has led to investigation into the evolutionary origins of the phl biosynthetic cluster. These analyses are aided by new genome sequences and some fascinating insights have been provided already. The finding that this metabolite, once considered a paradigm for a routine activity, is far more nuanced will sustain research in this area into the future.